Optical Microfiber Biomedical Sensors: Classification, Applications, and Future Perspectives - Lili Liang; Fei Xie; Li Jin; Bowen Yang; Li‐Peng Sun; Bai‐Ou Guan (Advanced Sensor Research)
Abstract Optical microfiber biosensors have emerged as a revolutionary technology in the biomedical field, offering exceptional sensitivity, specificity, and versatility for biomarkers detection, health monitoring, and disease treatment. This comprehensive review explores the diverse types of optical microfiber biosensors based on their fundamental principles and underscores their pivotal roles in biomedical advancements. Furthermore, the latest advancements and challenges faced by optical microfiber biosensors in their applications are scrutinized, offering insights into the future directions, potential breakthroughs, and hurdles that need to be addressed in the biomedical arena.